A Review of COVID-19 Chilblains-like Lesions and Their Differential Diagnoses. (July 2021) - Sachdeva, Muskaan; Mufti, Asfandyar; Maliyar, Khalad; Lara-Corrales, Irene; Salcido, Richard; Sibbald, Cathryn
Abstract : GENERAL PURPOSE: To familiarize wound care practitioners with the differential diagnoses of chilblains-like lesions that could be associated with the complications of COVID-19. TARGET AUDIENCE: This continuing education activity is intended for physicians, physician assistants, nurse practitioners, and nurses with an interest in skin and wound care. LEARNING OBJECTIVES/OUTCOMES: After participating in this educational activity, the participant will: 1. Identify the population most often affected by COVID toes. 2. Select the assessments that help differentiate the various conditions that cause chilblains-like lesions. 3. Choose appropriate treatment options for the various conditions that cause chilblains-like lesions. ABSTRACT: This review article focuses on the pathogenesis, clinical features, and diagnostic testing of the common pathologies that can manifest as chilblains-like lesions. These differentials include "COVID toes, " Raynaud phenomenon, acrocyanosis, critical limb ischemia, thromboangiitis obliterans, chilblains associated with lupus erythematosus, and idiopathic chilblains. The authors present a helpful mnemonic, ARCTIC, to assist clinicians in recognition and diagnosis.